(untitled) (CAHIERS MAGELLANES-NS, 2024)
This research article seeks to present an academic account of the working circumstances, lives of beedi workers and relevant Indian laws in the Jangipur Town region of West Bengal. The beedi manufacturing sector relies significantly on the labour-intensive process of beedi rolling, which is mostly performed by women and young girls. In contrast, males are typically engaged in duties such as sorting, inspecting, baking, labelling, packaging, and packing, which pay greater rates than beedi rolling. Despite the fact that beedi workers have been in the business for centuries, their occupational structure continues to remain unaltered, leaving the bulk of beedi rollers with a poor socioeconomic level and unpleasant living circumstances. Furthermore, tobacco use endangers the health of beedi workers, especially mothers and young girls. The purpose of this quantitative study is to throw light on the everyday life of beedi workers via in-depth interviews carried out in Murshidabad's Jangipur area with workers engaged in beedi rolling at their residences. The study demonstrates that a combination of factors including low levels of education, unemployment, inadequate earnings, limited mobility, and awful working conditions, as well as a lack of understanding of their rights, result in beedi workers being exploited and living in a state of perpetual poverty.